THE AMBIVALENCE OF MAIN CHARACTER IN DIVAKARUNI’S THE MISTRESS OF SPICES - Rosida, Ana; Petrina, Petrina (Study Program of English Literature, 2020)
This article analyzed of the ambivalence of the main character in the novel The Mistress of Spices by Chitra Banerjee Divakaruni by using post colonial theory from Bhabha concept that ambivalence, mimicry and hybridity. The purposes of this research were describing the cause of ambivalence by the main character and also to describe mimicry and hybridity potrayed by Tilo as the main character in Divakaruni’s The Mistress of Spices. The method of this research was descriptive qualitative methods to described the answer from the problem formulation. The source of the data of this research was the novel The Mistress of Spices by Chitra Banerjee Divakaruni which was published in 1997 and consists of 15 chapters and 317 pages. And, the instrument of this research was note taking. The technique of data analysis of this research was linked to the theory, concept and method. The result found that the main character face the ambivalence because of her rules and love. Living in America is greatly influenced her on the new culture of imitating and hybridizing about American culture.